Museum of thieves - Tanner, Lian (Tanner, Lian. Keepers trilogy, 2011)
Goldie, an impulsive and bold twelve-year-old, escapes the oppressive city of Jewel, where children are required to wear guardchains for their protection, and finds refuge in the extraordinary Museum of Dunt, an ever-shifting world where she discovers a useful talent for thievery and mysterious secrets that threaten her city and everyone she loves.